Constraining the recent history of the perennially ice-covered Lake Bonney, East Antarctica using He, Kr and Xe concentrations. (15th July 2017) - Hall, Chris M.; Castro, Maria Clara; Kenig, Fabien; Doran, Peter T.
Abstract: Lake Bonney is a perennially ice-covered lake in the McMurdo Dry Valleys (MDVs) that has long been studied in order to provide constraints on the paleoclimate of West Antarctica. The lake is divided into two lobes, West Lake Bonney (WLB) and East Lake Bonney (ELB) that are separated by a narrow ridge. The two lobes currently receive surface melt water during austral summers from glacier-fed ephemeral streams and this meltwater enters the lake via a narrow ring, or moat, of liquid water that forms around the lake during summer. The West Lobe also receives water from direct input of melt water from Taylor glacier and saline water from irregular subglacial discharge. Here, we combine previously published He data from Lake Bonney with new Kr and Xe concentration data to examine the signatures of water recharge via the seasonal moat and these data are used to constrain a model for He, Kr and Xe transport within both WLB and ELB over about the last 5000–6000 yrs. A detailed numerical simulation is presented that combines diffusive transport of noble gases within the stratified water column of Lake Bonney, along with ice ablation at the top of the ice cover, partitioning of noble gases between water and ice, plus exchange of noble gases between WLB and ELB. Results strongly suggest that open moats have only operated for about 2–3 centuries within the last millennium. These results are corroborated by the high concentration of He, especially within WLB, which points to a history of ice cover with no open moats operating for both lobes for at least about 5 millennia. In addition, the distribution of He, Kr and Xe suggest that a significant rise of the water level of Lake Bonney associated with a warmer period may have been interrupted by a roughly 4–5 century long cold period during which the moats were not large enough to allow air saturated water into the lake, with this cold period ending about one century ago. In addition, during this cold period, there is evidence for a thickening of the ice cover. In the last century Lake Bonney levels have been rising, pointing either to more extended austral summers or elevated summer temperatures, a rise that is compatible with the heavy noble gas record in the upper portion of the lake. A preliminary analysis that includes all stable noble gases heavier than He, suggests that glacial melt water (GMW) directly from Taylor Glacier below the ice cover may have been a significant input into the deepest parts of WLB, but not ELB.